International economics : understanding the forces of globalization for managers - Torelli, Paul. (2013 digital library., 2013)
Today's news media displays an intense fascination with the global economy--and for good reason. The degree of worldwide economic integration is unprecedented, and rising globalization has lifted living standards and reduced poverty. Foreign markets and new technologies continue to present opportunities for entrepreneurs and corporations. Still, economic shocks can spread across the world in minutes, impacting billions of lives. Citizens are understandably anxious in this age of macroeconomic turbulence and overextended governments. Modern economics offers a powerful framework for understanding globalization, international trade, and economic growth. Many managers possess years of hands-on experience dealing with business cycles and foreign competitive pressures, yet these leaders may not have a solid grounding in economic concepts that shed light on the forces of globalization. This book explains economics in everyday language, using little or no math, giving businesspersons better tools to interpret current events as well as long-term economic and political developments.